Pengaruh Model Pembelajaran Berbasis Masalah Terhadap Kemampuan Berpikir Kreatif Matematis Siswa - Simarmata, Justin Eduardo; Benu, Kristiani; Delvion, Eduardus Beo Seso (Program Studi Pendidikan Matematika, Fakultas Ilmu Pendidikan, Universitas Timor, 2024)
This study was motivated by the low creative thinking abilities of eighth-grade students at SMP Negeri 2 Amanatun Selatan. The purpose of the research was to analyze the effect of the problem-based learning (PBL) model on students' creative thinking skills. The population consisted of all eighth-grade students at SMP Negeri 2 Amanatun Selatan, with one class selected as the experimental group. The study employed a quasi-experimental method using a One-Group Pretest-Posttest Design. Data were collected through tests, and the analysis was conducted using a t-test. The findings indicated that the implementation of the problem-based learning model had a significant impact on students' creative thinking abilities. The significance value obtained was 0.001 (< 0.05), leading to the acceptance of the alternative hypothesis (H₁). Thus, it can be concluded that the problem-based learning model significantly improves the creative thinking abilities of eighth-grade students at SMP Negeri 2 Amanatun Selatan.